The effect of communication and implicit associations on consuming insects: An experiment in Denmark and Italy. (1st November 2016) - Verneau, Fabio; La Barbera, Francesco; Kolle, Susanne; Amato, Mario; Del Giudice, Teresa; Grunert, Klaus
Abstract: It has been widely noted that the introduction of insects in Westerns' diet might be a promising path towards a more sustainable food consumption. However, Westerns' are almost disgusted and sceptical about the eating of insects. In the current paper we report the results of an experiment conducted in two European countries—Denmark and Italy—different for food culture and familiarity with the topic of eating insects. We investigated the possibility to foster people's willingness to eat insect-based food through communication, also comparing messages based on individual vs. societal benefits of the eating of insects. Communication proved to be effective on intention and behaviour, and the societal message appeared to be more robust over time. The communication effect is significant across nation, gender, and previous knowledge about the topic. In addition, we investigated the impact of non-conscious negative associations with insects on the choice to eat vs. not eat insect-based food. Implicit attitudes proved to be a powerful factor in relation to behaviour, yet they did not impede the effectiveness of communication. Highlights: Communicating individual and social benefits of eating insects affects intention. Only social benefit message affects intention after two weeks. Communication has significant indirect effects on eating behaviour. Implicit associations with insects have significant direct effect on behaviour.